RE-DESAIN LAYOUT BUKU DUDAYA ALAM MINANGKABAU - Sabri Endrian; hendra afriwan (Universitas Negeri Padang, 2020)
Minangkabau custom is a value that governs all social life in Minangkabau. The book on natural Minangkabau culture is a reading that teaches the values of Minangkabau adat. The loss of local content in the 2013 curriculum made the community especially Minang begin to forget the values of this Minangkabau. Therefore, the writer makes a reading material for the Minangkabau natural culture book, which is a re-design of the Minangkabau natural culture book. The design is based on book theory, color, typography e 5W + 1H data analysis technique is (what, when where, who, why and how). In addition to designing the Minangkabau Natural Culture book as the main media, thisdesign has supporting media such as posters, x-banners, stickers, bookmarks, totebags, instagram feeds, and e-books.Keywords: Book, re-design, layout, natural Minangkabau culture